#### Answer

$x=-3$

#### Work Step by Step

By combining like terms and by using the properties of equality, the solution to the given equation, $
4x-6=6x
$, is
\begin{array}{l}\require{cancel}
4x-6x=6
\\\\
-2x=6
\\\\
x=\dfrac{6}{-2}
\\\\
x=-3
.\end{array}

Published by
Pearson

ISBN 10:
0-32184-874-8

ISBN 13:
978-0-32184-874-1

$x=-3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.